Decentralised approach of wastewater treatment and impact assessment of treated and untreated wastewater irrigation on agriculture land and its produce - Pal, Sumit; Patel, Neelam; Malik, Anushree; Singh, D K (The Indian Journal of Agricultural Sciences, 2020)
A field experiment was conducted from October, 2015 – March, 2017 to investigate the effects of drip irrigation with wastewater, and treated wastewater on crop quality at the 12-C Research farm of Indian Agriculture Research Institute, New Delhi. A bioreactor was installed at 12-C field for the purpose of cleaning the wastewater for the irrigation. After wastewater irrigation, the level of metals in the wastewater irrigated field got increased with time in the soil. While in treated water irrigated soil, concentration of metals was very less. In case of crops, the level of heavy metals was found more in wastewater irrigated crops than the treated water irrigated crops. From the study, it can be concluded that unlike treated wastewater, untreated wastewater cannot be used in agricultural land for a long time. Further, use of treated wastewater for irrigation does not have a negative impact on the consumers’ health as well.